Silicon carbide-based composite material containing adiabatic insulating ceramic hollow microspheres, preparation method and application thereof

CN122878152APending Publication Date: 2026-10-09NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610881806.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0008]针对现有技术存在的不足,本发明的目的在于,提供一种内含绝热绝缘陶瓷空心微球的碳化硅基复合材料、制备方法及其应用,解决现有技术中流道插件材料难以同时满足低热导率、低电导率与高力学性能、抗热冲击、耐辐照及长期服役可靠性要求的技术问题

Benefits of technology

(Ⅰ)本发明通过YSZ陶瓷空心微球本征低热导率降低热传导,以及封闭的小尺寸微孔抑制热对流和高温热辐射,三重隔热机制协同作用,显著提高材料的隔热效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878152A_ABST
    Figure CN122878152A_ABST
Patent Text Reader

Abstract

The application provides a silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres, a preparation method and application thereof, and belongs to the technical field of liquid blanket channel plug materials for nuclear fusion reactors. f The composite material is composed of a SiC / SiC composite material matrix and heat-insulating and insulating ceramic hollow microspheres; the heat-insulating and insulating ceramic hollow microspheres are yttria-stabilized zirconia ceramic hollow microspheres. f The preparation method adopts a vacuum impregnation method to introduce the heat-insulating and insulating ceramic hollow microspheres into the SiC / SiC composite material matrix. The application significantly improves the heat-insulating efficiency of the material through the triple heat-insulating mechanism of the intrinsic low thermal conductivity of the YSZ ceramic hollow microspheres, the suppression of heat convection and high-temperature heat radiation by the closed small-size micropores, and the synergistic effect of the three mechanisms. Meanwhile, the high-temperature insulating property of the YSZ ceramic hollow microspheres can effectively balance the adverse effect of the significant increase of the SiC conductivity at high temperatures, so that the electric insulating property of the composite material is not obviously weakened at high temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of liquid blanket flow channel plug-in materials for nuclear fusion reactors, and relates to SiC. f The invention relates to a silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres, its preparation method, and its application. Background Technology

[0002] In the liquid cladding module of nuclear fusion reactors, the current mainstream dual-cold cladding design uses low-activation ferritic / martensitic steel (RAFM) as the structural material and helium (or supercritical carbon dioxide) and liquid Pb-Li alloy as coolants. The liquid Pb-Li alloy simultaneously acts as a tritium breeder and neutron multiplier. However, when the liquid Pb-Li alloy flows at high speed in the strong magnetic field of nuclear fusion, it exhibits magnetohydrodynamic (MHD) effects, leading to additional MHD pressure drop problems. Furthermore, the safe operating temperature range of RAFM steel is limited (350–480 °C), while the outlet temperature of the liquid Pb-Li alloy in the dual-cold cladding design (>700 °C) far exceeds this range. To address these issues, a flow channel interlayer (FCI) is typically placed between the RAFM steel and the liquid Pb-Li alloy. This interlayer must simultaneously function as an electrical insulation layer (to suppress the MHD effect) and a thermal insulation layer (to protect the RAFM steel).

[0003] Nuclear-grade SiC prepared using chemical vapor infiltration (CVI) process f SiC composites possess excellent high-temperature mechanical properties, high-temperature chemical stability, radiation damage resistance, low activation characteristics, and low neutron absorption cross section, making them a candidate material for liquid blanket flow channel components in nuclear fusion reactors. However, as a wide bandgap semiconductor, SiC experiences valence band electrons gaining energy to transition to the conduction band at high temperatures, which can lead to... f The electrical conductivity of SiC composites at 400–1000 °C increases by 1–2 orders of magnitude compared to room temperature. Meanwhile, SiC prepared using existing CVI processes… f The thermal conductivity of SiC composites is generally higher than 12 W / (m·K) at 400–1000 °C. Therefore, SiC... f The physical properties of SiC composite materials currently cannot meet the requirements of flow channel inserts for thermal insulation (<5 W / (m·K)) and electrical insulation performance (<30 S / m). There is a need to improve the existing SiC composite materials. f The thermal insulation and electrical insulation properties of silicon carbide-based composite materials are of great significance for promoting the application of silicon carbide-based composite materials in the liquid blanket flow channel of nuclear fusion reactors and for the development of CFETR and future commercial nuclear fusion reactors.

[0004] SiC f / SiC composites, also known as continuous SiC fiber reinforced SiC matrix composites, have a significantly lower thermal conductivity (~10 W / (m·K)) than the SiC matrix (~60 W / (m·K)). Therefore, modifying the SiC matrix in composites is an effective way to improve their thermal insulation properties while ensuring that their mechanical properties do not significantly degrade. There are two main ways to improve the thermal insulation properties of the matrix: one is to increase the matrix porosity to delay heat convection and high-temperature thermal radiation; the other is to introduce a low thermal conductivity phase into the matrix to isolate heat conduction. However, excessively increasing the matrix porosity will cause the matrix to crack under low loads, thus affecting the overall load-bearing capacity of the material; introducing a low thermal conductivity phase into the matrix only isolates heat conduction and has limited effect on improving thermal insulation properties.

[0005] The existing technical solutions for improving the thermal insulation / insulation properties of silicon carbide-based composite materials and developing candidate materials for flow channel inserts, along with their disadvantages, are as follows: The first approach is a "sandwich" structure. This approach uses a gel casting method to prepare porous SiC ceramic as the core layer, and then uses chemical vapor deposition (CVD) to deposit a dense SiC coating of approximately 200 μm on its surface. This structure achieves good thermal insulation (thermal conductivity <10 W / (m·K)) and electrical insulation (conductivity <1 S / m) properties by utilizing the porous core layer. The disadvantages of this approach are: because the material has a non-dense porous structure and does not contain fibers to ensure strength and toughness, the overall strength is low and the thermal shock resistance is weak. During long-term service in high-temperature flowing liquid Pb-Li alloys, it is prone to breakage or local failure, leading to functional loss or even catastrophic damage.

[0006] The second approach involves a SiC ceramic-based composite flow channel insert. This method involves coating a mixed slurry containing polycarbosilane (a SiC precursor), SiC powder, ZrO2 powder, and Al2O3 powder onto a SiC prefabricated fabric with a pyrolytic carbon interface. A SiC matrix is ​​then deposited using CVI, and finally, a SiC coating is prepared via CVD. This material exhibits good thermal insulation properties (thermal conductivity <5 W / (m·K)). However, this approach has several drawbacks. To enhance the bonding between the powder and the fiber / matrix, 50%–60% polycarbosilane is added to the powder. Its high-temperature decomposition generates a large amount of free carbon and gaseous byproducts, leading to a near-stoichiometric reduction in the SiC matrix and the formation of numerous microcracks, thus decreasing radiation resistance and service reliability. Furthermore, the low thermal conductivity phase introduced in this approach is a fine powder. Its small size and tendency to agglomerate make it difficult to control the spatial distribution of the introduced phase, resulting in an uneven internal structure, large interlayer porosity, and poor bonding strength, ultimately compromising the material's mechanical properties.

[0007] The third approach involves a SiC-based composite material flow channel insert structure in a double-layer lithium-lead cooling device. This structure, from the inside out, comprises: a high-temperature PbLi liquid metal flow channel, a zirconia-doped SiC-based composite material, a liquid PbLi isolation layer, a steel alloy layer, and a helium cooling channel. Zirconia is doped into the SiC fiber layers in the form of long fibers, short fibers, or a continuous structure. The thermal insulation properties of zirconia allow for a temperature difference of 340–395 °C between the inside and outside of the insert, resulting in a maximum stress reduction of 30–500 MPa. The drawbacks of this approach are: its insulation mechanism relies solely on heat conduction, neglecting heat convection and high-temperature radiation, leading to lower insulation efficiency; and the zirconia continuous structure between the SiC fiber layers can weaken the interlayer bonding strength, affecting the overall mechanical properties. Summary of the Invention

[0008] To address the shortcomings of existing technologies, the present invention aims to provide a silicon carbide-based composite material containing thermally insulating ceramic hollow microspheres, its preparation method, and its application, thereby solving the technical problem that existing flow channel insert materials cannot simultaneously meet the requirements of low thermal conductivity, low electrical conductivity, high mechanical properties, thermal shock resistance, radiation resistance, and long-term service reliability.

[0009] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A method for preparing a silicon carbide-based composite material containing thermally insulating hollow ceramic microspheres, wherein the method incorporates thermally insulating hollow ceramic microspheres into SiC f Inside the SiC composite matrix, the traditional method of introducing a solid, low-thermal-conductivity phase is replaced with the introduction of a hollow, low-thermal-conductivity phase. These hollow, low-thermal-conductivity phases effectively fill the original matrix pore structure, dividing large pores into several smaller, closed pores, thus simultaneously blocking the three heat transfer pathways (heat convection, heat radiation, and heat conduction). Specifically, the steps include: Step 1: Preparation of SiC fiber preform with pyrolytic carbon (PyC) interface: Continuous SiC fibers are woven into SiC fiber cloth, which is then cut, flattened, layered, sewn, and edge-locked to form a SiC fiber preform. Subsequently, a pyrolytic carbon interface is deposited on the SiC fiber preform using a chemical vapor infiltration process. After deposition, a SiC fiber preform with a pyrolytic carbon interface is obtained.

[0010] Step 2, Preparation of ceramic hollow microsphere impregnation slurry: Add a dispersing binder to the solvent, then add the heat-insulating and insulating ceramic hollow microspheres, and stir to obtain the impregnation slurry.

[0011] Step 3, Pre-deposition of SiC matrix: The SiC fiber preform with pyrolytic carbon interface obtained in Step 1 is pre-deposited using a chemical vapor infiltration process to obtain semi-dense SiC. f / SiC composite material.

[0012] Step 4, Introduce thermally insulating ceramic hollow microspheres: The semi-dense SiC prepared in Step 3 is then... f The SiC composite material is completely immersed in the impregnation slurry prepared in step two, introducing thermally insulating ceramic hollow microspheres into the SiC. f In SiC composite materials, a semi-dense silicon carbide-based composite material containing thermally insulating ceramic hollow microspheres is obtained.

[0013] Step 5, Densification of SiC Matrix by Chemical Vapor Infiltration Deposition: The semi-dense silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres prepared in Step 4 is deposited using a chemical vapor infiltration process to obtain a dense silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres.

[0014] This invention also protects a silicon carbide-based composite material containing thermally insulating ceramic hollow microspheres, prepared by the method described above. This material is made of SiC. f It is composed of SiC composite materials and thermally insulating ceramic hollow microspheres.

[0015] This invention also protects the application of the silicon carbide-based composite material containing thermally insulating ceramic hollow microspheres as described above in the preparation of liquid blanket flow channel plugs for nuclear fusion reactors.

[0016] The present invention also has the following technical features: Specifically, in step one, the fiber density of the fiber cloth in both the warp and weft directions is 8-10 fibers / cm.

[0017] Specifically, in step one, the structure of the SiC fiber preform is 2D, 2.5D, or 3D.

[0018] Specifically, in step one, the volume fraction of SiC fibers in the SiC fiber preform is 35 vol.%, and the density is approximately 1.0 g / cm³. 3 .

[0019] Specifically, in step one, the thickness of the pyrolytic carbon interface is 50–200 nm.

[0020] Specifically, in step one, the chemical vapor infiltration process parameters used for depositing the PyC interface are as follows: the precursor gas source is propylene, Ar is the diluent gas, the pressure is 2-3 kPa, the temperature is 850-1000 ℃, and the deposition time is 90-100 hours.

[0021] Specifically, in step two, the solvent is ultrapure water or anhydrous ethanol.

[0022] Specifically, in step two, the dispersing binder is selected from one or more combinations of carboxymethyl cellulose, polyvinyl alcohol, and polyvinyl butyral.

[0023] Specifically, in step two, the content of the dispersant binder in the impregnation slurry is 1.0 to 1.5 wt.%, and the mass ratio of the heat-insulating and insulating ceramic hollow microspheres to the solvent is 1:2 to 2:1.

[0024] Specifically, in step two, the viscosity of the impregnation slurry is 250–600 mPa·s. Preferably, the viscosity of the impregnation slurry is 270–480 mPa·s.

[0025] Specifically, in step two, the stirring time is more than 4 hours. Preferably, the stirring time is 4 to 8 hours.

[0026] Specifically, in step three, the parameters for pre-deposition using chemical vapor infiltration are as follows: the precursor gas source is trichloromethylsilane, Ar is the dilution gas, H2 is the carrier gas, the pressure is 2-3 kPa, and the temperature is 950-1050 ℃.

[0027] Specifically, in step three, semi-dense SiC f The density of the SiC composite material is 1.0–2.0 g / cm³. 3 (Density 1.0 g / cm³) 3 It can be directly the fiber preform prepared in step one).

[0028] Specifically, in step four, the amount of heat-insulating and insulating ceramic hollow microspheres introduced is 10–30 vol.%.

[0029] Specifically, in step four, the method for introducing the heat-insulating and insulating ceramic hollow microspheres is selected from vacuum impregnation, pressure impregnation, ultrasonic impregnation, isostatic impregnation, or centrifugal impregnation; or selected from one or more combinations of manual brushing, dip coating, spraying, spin coating, scraping coating, roller coating, and screen printing.

[0030] Preferably, in step four, the heat-insulating hollow ceramic microspheres are introduced using a vacuum impregnation method, under the following conditions: vacuum degree of -0.096 MPa to -0.099 MPa, single impregnation time of 10 to 40 min, and number of impregnations of 1 to 12. Most preferably, the single impregnation time is 10 to 20 min, and the number of impregnations is 1 to 10.

[0031] Specifically, in step five, the parameters for deposition using chemical vapor infiltration are exactly the same as those in step three.

[0032] Specifically, in step five, if the weight gain of a batch of samples is less than 5% during the deposition process, the upper and lower surfaces of the sample need to be ground to open the surface pores, and then deposition can continue to gradually densify the interior of the matrix. During this period, the porosity of the composite material is measured by the drainage method until the porosity is less than 10%.

[0033] Specifically, in step five, the density of the resulting dense silicon carbide-based composite material containing thermally insulating ceramic hollow microspheres is ≥2.5 g / cm³. 3 .

[0034] Specifically, the heat-insulating and insulating ceramic hollow microspheres are yttrium-stabilized zirconia (YSZ) ceramic hollow microspheres with a thermal conductivity of <1 W / (m·K) and an electrical conductivity of <10 S / m; their shape is nearly spherical, with a particle size D50 of 30 to 60 µm and a wall thickness of 3 to 8 µm.

[0035] Specifically, the preparation method of yttrium oxide stabilized zirconia ceramic hollow microspheres is selected from one or more of the following methods: template method, spray drying method, foaming method, and aerosol-assisted method.

[0036] Optionally, one or more of the following materials can be used to partially or completely replace the yttrium-stabilized zirconia ceramic hollow microspheres: zirconia ceramic hollow microspheres, silica ceramic hollow microspheres, alumina ceramic hollow microspheres, aluminum silicate ceramic hollow microspheres, mullite ceramic hollow microspheres, and silicon carbide ceramic hollow microspheres.

[0037] Compared with the prior art, the present invention has the following technical effects: (I) The present invention reduces heat conduction by means of the intrinsic low thermal conductivity of YSZ ceramic hollow microspheres, and suppresses heat convection and high-temperature heat radiation by means of closed small-sized micropores. The triple heat insulation mechanism works synergistically to significantly improve the heat insulation efficiency of the material.

[0038] (II) The YSZ ceramic hollow microspheres used in this invention have excellent high-temperature insulation properties, which can effectively balance the adverse effects of the significant increase in SiC conductivity at high temperatures, so that the electrical insulation performance of the composite material is not significantly weakened at high temperatures.

[0039] (III) The YSZ ceramic hollow microspheres used in this invention can buffer volume changes, alleviate residual stress, and reduce the number and size of initial microcracks; interrupt the continuous SiC matrix to hinder crack propagation; when the crack encounters the YSZ ceramic hollow microspheres, it is deflected or the tip enters the hollow interior and becomes blunt (pinning effect), which increases the matrix cracking stress and enables the material to maintain high strength and excellent reliability.

[0040] (IV) By adjusting the particle size, volume fraction and density of the pre-deposited SiC matrix, the present invention can control the spatial distribution of YSZ ceramic hollow microspheres in the matrix, improve interlayer bonding and structural uniformity, and meet different performance indicators and component structure requirements.

[0041] (V) The YSZ ceramic hollow microspheres used in this invention have the advantages of high temperature resistance, radiation resistance, and low activation. CVI deposition produces no byproducts, and the SiC matrix remains pure and close to stoichiometry, making it suitable for nuclear fusion nuclear material applications. It is highly compatible with existing CVI processes and can manufacture complex and precision components, continuing the traditional SiC... f The range of possible fabrication methods for SiC composite components.

[0042] (VI) The SiC finally obtained by this invention f The (SiC+YSZ) composite material combines thermal insulation, electrical insulation, and high strength and toughness, which can meet the requirements for use in liquid blanket flow channel components of nuclear fusion reactors. Attached Figure Description

[0043] Figure 1 This is a process flow diagram of the present invention.

[0044] Figure 2 This is a scanning electron microscope image of YSZ ceramic hollow microspheres.

[0045] Figure 3 SiC f Schematic diagram of the construction of a (SiC+YSZ) composite material structure. (a) Semi-dense SiC f / SiC composites; (b) Semi-dense SiC f / (SiC+YSZ) composite material; (c) SiC f / (SiC+YSZ) composite material.

[0046] Figure 4 SiC f CT images of the (SiC+YSZ) composite material. (a) 10 vol.% YSZ; (b) 20 vol.% YSZ; (c) 30 vol.% YSZ.

[0047] Figure 5 SiC f Tensile strength and matrix cracking stress of (SiC+YSZ) composite material.

[0048] Figure 6 SiC f Mechanical fracture diagram of (SiC+YSZ) composite material.

[0049] Figure 7 SiC f Thermal conductivity of (SiC+YSZ) composite materials.

[0050] Figure 8 SiC f Electrical conductivity of the (SiC+YSZ) composite material.

[0051] The specific content of the present invention will be further explained in detail below with reference to the embodiments. Detailed Implementation

[0052] It should be noted that, unless otherwise specified, all raw materials used in this invention are those known in the art.

[0053] In this invention, some abbreviations are explained as follows: SiC f / SiC composites refer to SiC-based composites reinforced with continuous SiC fibers. The matrix of this composite material is SiC ceramic, with SiC fibers serving as the reinforcement, providing the material with the main strength and toughness, especially the ability to resist crack propagation. This overcomes the inherent shortcomings of traditional silicon carbide ceramics, such as high brittleness, sensitivity to defects, and susceptibility to catastrophic fracture, and exhibits excellent mechanical properties.

[0054] YSZ hollow ceramic microspheres refer to yttria-stabilized zirconia (YSZ) hollow ceramic microspheres.

[0055] SiC f / (SiC+YSZ) composite material refers to a continuous SiC fiber reinforced SiC and YSZ ceramic matrix composite material, in SiC f The SiC composite material incorporates YSZ ceramic hollow microspheres into a SiC ceramic matrix. The matrix of this composite material is a combination of SiC ceramic and YSZ ceramic hollow microspheres, making it a silicon carbide-based composite material that combines thermal insulation, electrical insulation, and high strength and toughness.

[0056] The technical concept and principle of this invention are as follows: This invention addresses existing SiC... f The matrix of SiC composites is modified by introducing thermally insulating and insulating YSZ ceramic hollow microspheres into the matrix. Utilizing their closed hollow structure and dispersed distribution characteristics, the large pores in the material are divided into several closed micropores, constructing a novel matrix structure in which closed micropores are dispersed in the interlayer pores, thus achieving a structure-function integrated SiC matrix. f / (SiC+YSZ) composite material. By changing the traditional method of introducing a solid, low-thermal-conductivity phase to introducing a hollow, low-thermal-conductivity phase, YSZ ceramic hollow microspheres effectively fill the original matrix pores, dividing large pores into several smaller, closed pores. This simultaneously blocks three heat transfer pathways: heat conduction, heat convection, and high-temperature heat radiation, forming a triple insulation mechanism. The inherently low thermal and electrical conductivity of YSZ ceramic hollow microspheres suppresses heat and electrical conduction, while optimizing pore distribution and sealing micropores to inhibit heat convection and high-temperature heat radiation. The high-temperature insulation properties of YSZ ceramic hollow microspheres balance the increase in SiC conductivity at high temperatures, maintaining high-temperature electrical insulation performance.

[0057] In terms of mechanics, this invention utilizes YSZ ceramic hollow microspheres to provide buffer space for changes in matrix volume, thereby alleviating residual stress and reducing initial microcracks. The uniformly dispersed YSZ ceramic hollow microspheres divide the continuous SiC matrix, hindering crack propagation. Furthermore, through crack deflection and the entry of the crack tip into the hollow core, a "pinning" effect is formed, increasing cracking stress, maintaining high strength, and improving reliability.

[0058] In this invention, YSZ ceramic hollow microspheres are introduced through vacuum impregnation, combined with mature CVI technology for interface deposition and SiC matrix densification. By controlling the particle size, volume fraction, and density of the pre-deposited SiC matrix of the YSZ ceramic hollow microspheres, the spatial distribution of the YSZ ceramic hollow microspheres is changed, resulting in good interlayer bonding and structural uniformity, achieving flexible processing and adjustable performance.

[0059] Because YSZ ceramic hollow microspheres are heat-resistant, radiation-resistant, have low activation, and possess certain mechanical strength, they produce no byproducts during the CVI process, keeping the SiC matrix pure and close to stoichiometry. Furthermore, the preparation process is similar to existing SiC... f The CVI process parameters of the / SiC composite material are well matched, which can produce components with precise dimensions and complex structures, providing new design ideas for the liquid blanket flow channel plug-in material system of nuclear fusion reactor.

[0060] Following the above technical approach, specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent modifications made based on the technical solutions of this application fall within the protection scope of the present invention.

[0061] Example 1: This embodiment provides a method for preparing a silicon carbide-based composite material containing thermally insulating ceramic hollow microspheres, such as... Figure 1 As shown, this method introduces thermally insulating and insulating hollow ceramic microspheres into SiC. fWithin the SiC composite matrix, YSZ ceramic hollow microspheres are selected as the introduced thermally insulating and insulating ceramic hollow microspheres, and vacuum impregnation is chosen as the introduction process. Specifically, the process includes the following steps: Step 1: Prepare a SiC fiber preform with a pyrolytic carbon (PyC) interface: Step 1.1, Preparation of SiC fiber preform: SiC fibers are woven into SiC fiber cloth, with a fiber density of 8-10 fibers / cm in both the warp and weft directions; the SiC fiber cloth is cut and flattened and layered with the same size, then sewn and edge-locked using continuous carbon fiber to form the SiC fiber preform; the volume fraction of SiC fibers in the SiC fiber preform is approximately 35 vol.%, and the density is approximately 1.0 g / cm³. 3 .

[0062] Step 1.2: Preparation of SiC fiber preform with PyC interface: A PyC interface is deposited on the SiC fiber preform obtained in Step 1.1 using the CVI process. The thickness of the pyrolytic carbon interface is 50–200 nm. The parameters for depositing the PyC interface are as follows: the precursor gas source is propylene (C3H6), Ar is the diluent gas, the pressure is 2–3 kPa, the temperature is 850–1000 ℃, and the deposition time is 90–100 hours. After deposition, a SiC fiber preform with a PyC interface is obtained.

[0063] Step 2, Preparation of ceramic hollow microsphere impregnation slurry: Carboxymethyl cellulose was added to ultrapure water as a dispersant and binder, followed by an appropriate proportion of YSZ ceramic hollow microspheres. The YSZ ceramic hollow microspheres were nearly spherical in shape, with a particle size (D50 = 30–60 µm) and a wall thickness of 3–8 µm. Figure 2 This is a scanning electron microscope image of YSZ ceramic hollow microspheres. The mixture was then stirred using a magnetic / mechanical stirrer for at least 4 hours to obtain a uniformly dispersed impregnation slurry with good flowability. In this embodiment, to systematically optimize the preparation process of the YSZ ceramic hollow microsphere impregnation slurry, the synergistic effects of two key process parameters—carboxymethyl cellulose content and the mass ratio of YSZ ceramic hollow microspheres to ultrapure water—on the impregnation slurry (using slurry viscosity as an indicator) were investigated. Specific process parameters are shown in Table 1.

[0064] Step 3, Pre-deposit SiC substrate: The SiC fiber preform with a PyC interface prepared in step one was placed in a deposition furnace, and the SiC matrix was pre-deposited using the CVI process. The precursor gas source was trichloromethylsilane (CH3SiCl3), Ar was used as the dilution gas, and H2 was used as the carrier gas. The pressure was 2-3 kPa, and the temperature was 950-1050 °C, resulting in semi-dense SiC. f The structural schematic diagram of the / SiC composite material is shown below. Figure 3 As shown in (a). In this embodiment, the process parameters for step three are as follows: semi-dense SiC f The density of the SiC composite material is 1.0 g / cm³. 3 .

[0065] Step 4: Introduce heat-insulating and insulating ceramic hollow microspheres: The semi-dense SiC prepared in step three f The SiC composite material is completely immersed in the impregnation slurry prepared in step two, and YSZ ceramic hollow microspheres are introduced by vacuum impregnation to obtain semi-dense SiC. f The (SiC+YSZ) composite material can incorporate different volume fractions (10 vol.%–30 vol.%) of YSZ ceramic hollow microspheres by adjusting the impregnation time and number of impregnation cycles to meet the needs of various applications. A schematic diagram of its structure is shown below. Figure 3 As shown in (b). In this embodiment, the process parameters for step four are as follows: vacuum degree is -0.096 MPa to -0.099 MPa, single immersion time is 20 min, and the number of immersions is 1 to 7.

[0066] Step 5, CVI deposition and SiC matrix densification: Using the same CVI process parameters as in step three, the semi-dense SiC prepared in step four was processed... f The SiC+YSZ composite material was deposited. During the deposition process, if the weight gain of the sample in one batch was less than 5%, the upper and lower surfaces of the sample needed to be ground to open the surface pores. Deposition continued to gradually densify the matrix. During this process, the open porosity of the composite material was measured using the water displacement method until the open porosity was less than 10%, thus obtaining a dense SiC matrix. f The structural schematic diagram of the (SiC+YSZ) composite material is shown below. Figure 3 As shown in (c). The SiC fabricated f The density of the (SiC+YSZ) composite material is ≥2.5 g / cm³. 3 .

[0067] Table 1. Viscosity Comparison of Different Slurry Ratios

[0068] Experimental results show that the YSZ ceramic hollow microspheres to ultrapure water (wt.%) ratios in impregnation slurries 7-9 and 12-14 in Table 1 range from 1:2 to 2:1, the carboxymethyl cellulose content ranges from 1.0 to 1.5 wt.%, and the slurry viscosity ranges from 270 to 480 mPa·s. These slurries exhibit suitable impregnation viscosity, are uniformly dispersed, and have good fluidity, making them the most suitable impregnation slurries. Slurries 1-6 and 11, due to their lower viscosity, show rapid sedimentation and stratification. Slurries 10 and 15, due to their higher YSZ ceramic hollow microsphere content, suffer from insufficient support for all the YSZ ceramic hollow microspheres by the three-dimensional network structure constructed by the binder, resulting in agglomeration and stratification. Slurries 16-20, due to their higher viscosity, poor fluidity, and agglomeration, are unsuitable as impregnation slurries. In summary, step two, by optimizing the slurry ratio, obtained the optimal range of impregnation slurry ratios, laying the foundation for subsequent impregnation experiments.

[0069] Example 2: This embodiment provides a method for preparing a silicon carbide-based composite material containing thermally insulating ceramic hollow microspheres, including the following steps: Step 1: Preparation of SiC fiber preform with pyrolytic carbon (PyC) interface: exactly the same as Step 1 in Example 1.

[0070] Step 2, Preparation of ceramic hollow microsphere impregnation slurry: This is basically the same as Step 2 in Example 1, except that in this example, the impregnation slurry used contains YSZ ceramic hollow microspheres: ultrapure water (wt.%) = 1:1, and the content of carboxymethyl cellulose is 1 wt.%.

[0071] Step 3, Pre-depositing SiC substrate: This is basically the same as step 3 in Example 1, except that in this example, semi-dense SiC is deposited. f The density of the SiC composite material is 1.5 g / cm³. 3 .

[0072] Step 4: Introduce heat-insulating and insulating ceramic hollow microspheres: The process is basically the same as step four in Example 1. The difference is that in this example, the synergistic effect of two key process parameters, impregnation time and number of impregnations, on impregnation efficiency (indicated by the volume fraction of YSZ ceramic hollow microspheres introduced during impregnation) is examined. The specific process parameters are shown in Table 2.

[0073] Step 5, CVI deposition and SiC substrate densification: This is exactly the same as step 5 in Example 1.

[0074] Table 2. Comparison of Impregnation Efficiency

[0075] The experimental results show that when the single impregnation time is 10 min, after 10 impregnations (number 3), the volume fraction of YSZ hollow ceramic microspheres introduced by impregnation is close to saturation, with a total impregnation time of 100 min; when the single impregnation time is 20 min, after 6 impregnations (number 7), the volume fraction of YSZ hollow ceramic microspheres introduced by impregnation is close to saturation, with a total impregnation time of 120 min; when the single impregnation time is 30 min, after 6 impregnations (number 11), the volume fraction of YSZ hollow ceramic microspheres introduced by impregnation is 30.0 vol.%, with a total impregnation time of 180 min. Compared with numbers 3 and 7, the total impregnation time is lower for the same introduced volume fraction; when the single impregnation time is 40 min, after 5 impregnations (number 14), the volume fraction of YSZ hollow ceramic microspheres introduced by impregnation is 30.1 vol.%. At vol.%, the total impregnation time is 200 min. Compared with items 3 and 7, with the same volume fraction introduced, the total impregnation time of items 3 and 7 is lower. In summary, from the perspective of impregnation efficiency and energy saving and emission reduction, the single impregnation time range is 10-20 min, and the number of impregnations ranges ≤10 times.

[0076] Example 3: This embodiment provides a method for preparing a silicon carbide-based composite material containing thermally insulating ceramic hollow microspheres, including the following steps: Step 1: Preparation of SiC fiber preform with pyrolytic carbon (PyC) interface: exactly the same as Step 1 in Example 1.

[0077] Step 2, Preparation of ceramic hollow microsphere impregnation slurry: This is basically the same as Step 2 in Example 1, except that in this example, the impregnation slurry used contains YSZ ceramic hollow microspheres: ultrapure water (wt.%) = 1:1, and the content of carboxymethyl cellulose is 1 wt.%.

[0078] Step 3, Pre-deposit SiC substrate: This step is basically the same as step 3 in Example 1, except that in this example, to systematically optimize the process parameters for pre-depositing the SiC substrate, the focus is on examining the semi-dense SiC substrate after pre-depositing in step 3. f The influence of the density of the / SiC composite material on the uniformity of subsequent impregnation (indicated by the distribution of YSZ ceramic hollow microspheres inside the material) is shown in Table 3 for specific process parameters.

[0079] Step four, introduce heat-insulating and insulating ceramic hollow microspheres: exactly the same as step four in Example 1.

[0080] Step 5, CVI deposition and SiC substrate densification: This is exactly the same as step 5 in Example 1.

[0081] Table 3. Comparison of Impregnation Uniformity

[0082] Experimental results show that the YSZ ceramic hollow microspheres prepared in items 1 to 8 are uniformly distributed and dispersed without agglomeration within the material. Among them, the semi-dense SiC used for impregnation in items 4 to 6 is particularly well-developed. f The density of the SiC composite material is 1.5 g / cm³. 3 The SiC produced f The open porosity of the (SiC+YSZ) composite material is relatively low, approximately 5%, as shown in the CT image. Figure 4 As shown. The semi-dense SiC used for impregnation in items 10-11. f The high density of SiC composite materials makes it difficult for YSZ ceramic hollow microspheres to penetrate the internal pores of the material during impregnation, resulting in SiC... f In the (SiC+YSZ) composite material, the YSZ ceramic hollow microspheres are unevenly distributed, mostly piled up on the surface, exhibiting a phenomenon of less in the middle layer and more on the surface. Therefore, from the perspective of the uniformity of internal distribution of the material, a density range of 1.0–2.0 g / cm³ is selected. 3 Semi-dense SiC f Impregnation experiments were conducted on the SiC composite material.

[0083] Figure 4 SiC f CT image of the (SiC+YSZ) composite material. It can be seen that the YSZ ceramic hollow microspheres are uniformly distributed in the composite material and can maintain the hollow structure.

[0084] Figure 5 , Figure 6 , Figure 7 and Figure 8 The SiC prepared according to the present invention f The mechanical strength, mechanical fracture surface, thermal conductivity, and electrical conductivity of the (SiC+YSZ) composite material are shown in the diagram. The YSZ ceramic hollow microspheres used have a particle size D50 of 60 µm and an average wall thickness of 10 µm, and are impregnated with semi-dense SiC. f The density of the SiC composite material is 1.5 g / cm³. 3 The volume percentages of YSZ ceramic hollow microspheres obtained were 10 vol.%, 20 vol.%, and 30 vol.% SiC. f / (SiC+YSZ) composite material.

[0085] Figure 5 It can be seen that the SiC prepared by this invention f The tensile strength of the (SiC+YSZ) composite material is well maintained, and the matrix cracking stress is lower than that of pure SiC. fThe SiC composite material showed improved performance; when the YSZ ceramic hollow microsphere content was 20 vol.%, the tensile strength was ~355 MPa and the matrix cracking stress was ~162 MPa, comparable to pure SiC. f The SiC composite material (~400 MPa) retains ~88% of its strength, while the matrix cracking stress is lower than that of pure SiC. f The SiC composite material improved by ~33%, maintaining the high strength of the composite material and enhancing its crack resistance.

[0086] Figure 6 It can be seen that a large number of SiC fibers were pulled out during stretching, proving that the addition of YSZ ceramic hollow microspheres preserved the SiC. f The SiC composite material exhibits high strength and toughness. Furthermore, when crack propagation encounters YSZ hollow ceramic microspheres, some cracks deflect along the weak interface between the YSZ microspheres and the SiC matrix, causing interface debonding and lengthening the crack propagation path, thus consuming crack propagation energy. Other cracks penetrate the hollow interior of the microspheres, blunting the crack tip and creating a "pinning" effect. Therefore, the introduction of YSZ hollow ceramic microspheres not only preserves the SiC... f The inherent strength and toughness of the SiC composite material are enhanced, while the cracking stress of the matrix is ​​also increased, further improving the reliability of the material.

[0087] Figure 7 It can be seen that SiC with 0 vol.% YSZ content f The thermal conductivity of the SiC composite material is approximately 12–15 W / (m·K) at room temperature to 700 °C. The SiC prepared in this invention… f The thermal conductivity of the (SiC+YSZ) composite material decreased significantly from room temperature to 700 ℃. Among them, the composite materials with YSZ content of 20 vol.% and 30 vol.% had similar thermal conductivity from room temperature to 700 ℃, both <5 W / (m·K), and had good thermal insulation effect.

[0088] Figure 8 It can be seen that, since SiC itself is a semiconductor, SiC with 0 vol.% YSZ content... f The conductivity of the / SiC composite material is about 10 to 62 S / m at room temperature to 700 ℃. By introducing thermally insulating YSZ ceramic hollow microspheres, the conductivity is significantly reduced by about 2 to 5 times.

Claims

1. A method for preparing a silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres, characterized in that, This method introduces thermally insulating ceramic hollow microspheres into SiC f / Inside the SiC composite matrix; The method includes the following steps: Step 1: Preparation of SiC fiber preforms with pyrolytic carbon interfaces: Step 2, Preparation of ceramic hollow microsphere impregnation slurry: Add dispersing binder to solvent, then add heat-insulating and insulating ceramic hollow microspheres, stir to obtain impregnation slurry; Step 3, Pre-deposition of SiC matrix: The SiC fiber preform with pyrolytic carbon interface obtained in Step 1 is pre-deposited using a chemical vapor infiltration process to obtain semi-dense SiC. f / SiC composite materials; Step 4, Introduce thermally insulating ceramic hollow microspheres: The semi-dense SiC prepared in Step 3 is then... f The SiC composite material is completely immersed in the impregnation slurry prepared in step two, and the heat-insulating and insulating ceramic hollow microspheres are introduced into the SiC through vacuum impregnation. f In SiC composite materials, a semi-dense silicon carbide-based composite material containing thermally insulating hollow ceramic microspheres was obtained. Step 5, Densification of SiC Matrix by Chemical Vapor Infiltration Deposition: The semi-dense silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres prepared in Step 4 is deposited using a chemical vapor infiltration process to obtain a dense silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres.

2. The method for preparing the silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres as described in claim 1, characterized in that, In step two, the solvent is ultrapure water or anhydrous ethanol; the dispersing binder is selected from one or more combinations of carboxymethyl cellulose, polyvinyl alcohol, and polyvinyl butyral; and the heat-insulating and insulating ceramic hollow microspheres are yttrium oxide-stabilized zirconia ceramic hollow microspheres. In step two, the content of the dispersing binder in the impregnation slurry is 1.0 to 1.5 wt.%, and the mass ratio of the thermal insulation ceramic hollow microspheres to the solvent is 1:2 to 2:

1.

3. The method for preparing the silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres as described in claim 1, characterized in that, In step three, semi-dense SiC f The density of the SiC composite material is 1.0–2.0 g / cm³. 3 In step four, the amount of heat-insulating and insulating ceramic hollow microspheres introduced is 10–30 vol.%.

4. The method for preparing the silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres as described in claim 1, characterized in that, In step four, the heat-insulating and insulating ceramic hollow microspheres are introduced using a vacuum impregnation method under the following conditions: vacuum degree of -0.096 MPa to -0.099 MPa, single impregnation time of 10 to 40 min, and number of impregnations of 1 to 12.

5. The method for preparing the silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres as described in claim 1, characterized in that, In step three, the parameters for pre-deposition using chemical vapor infiltration are as follows: the precursor gas source is trichloromethylsilane, Ar is the dilution gas, H2 is the carrier gas, the pressure is 2-3 kPa, and the temperature is 950-1050 ℃. In step five, the parameters for deposition using chemical vapor infiltration are exactly the same as those in step three.

6. The method for preparing the silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres as described in claim 1, characterized in that, Step one specifically involves: weaving continuous SiC fibers into SiC fiber cloth, and then sequentially cutting, flattening and layering, sewing and hemming to produce a SiC fiber preform; subsequently, a pyrolytic carbon interface is deposited on the SiC fiber preform using a chemical vapor infiltration process, and after the deposition is completed, a SiC fiber preform with a pyrolytic carbon interface is obtained.

7. The method for preparing the silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres as described in claim 6, characterized in that, In step one, the volume fraction of SiC fibers in the SiC fiber preform is 35 vol.%, and the density is 1.0 g / cm³. 3 .

8. The method for preparing the silicon carbide-based composite material containing heat-insulating and insulating ceramic hollow microspheres as described in claim 6, characterized in that, In step one, the chemical vapor infiltration process parameters are as follows: the precursor gas source is propylene, Ar is the diluent gas, the pressure is 2-3 kPa, the temperature is 850-1000 ℃, and the deposition time is 90-100 hours.

9. A silicon carbide-based composite material containing thermally insulating ceramic hollow microspheres, prepared by the method according to any one of claims 1 to 8, characterized in that, From SiC f The structure consists of a SiC composite matrix and thermally insulating hollow ceramic microspheres; the thermally insulating hollow ceramic microspheres are yttrium oxide stabilized zirconia ceramic hollow microspheres.

10. The application of the silicon carbide-based composite material containing thermally insulating ceramic hollow microspheres as described in claim 9 in the preparation of liquid blanket flow channel components for nuclear fusion reactors.